PBL project reflection: Challenges in communicating change - Yusof, Norhafezah; Awang Hashim, Rosna; Nordin, Hasniza; Abdul Rahim, Fauziah; Shaik Abdullah, Sarimah; Wan Din, Wan Zalina (Universiti Putra Malaysia Press, 2011)
The objective of this paper is to discuss challenges of implementing a Project Based Learning (PBL) approach at three selected schools in one of the northern states in Malaysia.For this purpose, semi-structured interviewing and observation methods were employed.The data were analyzed based on the Five Sentiments Approach (Armenakis, Harris, Cole, Lawrence & Self, 2007a).The findings revealed that there was a high resistance from the teachers and students towards change due to the blatant exam-oriented culture which was still practiced in Malaysian educational institutions.